2008
DOI: 10.1523/jneurosci.5530-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Continuous  -Opioid Receptor Activation Reduces Neuronal Voltage-Gated Sodium Channel (NaV1.7) Levels through Activation of Protein Kinase C in Painful Diabetic Neuropathy

Abstract: The Na V 1.7 tetrodotoxin-sensitive voltage-gated sodium channel isoform plays a critical role in nociception. In rodent models of diabetic neuropathy, increased Na V 1.7 in dorsal root ganglia (DRG) neurons correlates with the emergence of pain-related behaviors characteristic of painful diabetic neuropathy (PDN). We examined the effect of transgene-mediated expression of enkephalin on pain-related behaviors and their biochemical correlates in DRG neurons. Transfection of DRG neurons by subcutaneous inoculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 48 publications
6
110
1
1
Order By: Relevance
“…27 Thermal hyperalgesia in STZ-diabetic rats was prevented or reversed by the AR inhibitor lidorestat, 19 the AGE formation inhibitor pyridoxamine, 25 the PKC LY333531, 26 several antioxidants (including ␣-lipoic acid, 20 the hydroxyl radical scavenger dimethylthiourea, 21 the xanthine oxidase inhibitor allopurinol, 28 and taurine 29 ), the PARP inhibitors 1,5-isoquinolinediol 12 and nicotinamide, 30 and the neurocytokine interleukin-6, 31 as well as by transgene-mediated expression of enkephalin in dorsal root ganglia neurons. 32 C-peptide and the glutamate carboxypeptidase II inhibitor treatments alleviated thermal hyperalgesia in type 1 diabetic BB/ Wor rats, 27,33 and taurine in type 2 Zucker diabetic fatty rats. 34 Whereas mechanisms underlying analgesic effect of these agents require further studies, a number of the treatments mentioned here have been reported to counteract glutamate excitotoxicity by reducing glutamate accumulation, 33,35,36 to restore impaired Ca 2ϩ homeostasis and signaling, 37 to inhibit mitogen-activated protein kinase (MAPK) activation, 38 and to counteract production of proinflammatory cytokines.…”
Section: Pathogenesis and Experimental Treatments Of Diabetes-associamentioning
confidence: 91%
See 2 more Smart Citations
“…27 Thermal hyperalgesia in STZ-diabetic rats was prevented or reversed by the AR inhibitor lidorestat, 19 the AGE formation inhibitor pyridoxamine, 25 the PKC LY333531, 26 several antioxidants (including ␣-lipoic acid, 20 the hydroxyl radical scavenger dimethylthiourea, 21 the xanthine oxidase inhibitor allopurinol, 28 and taurine 29 ), the PARP inhibitors 1,5-isoquinolinediol 12 and nicotinamide, 30 and the neurocytokine interleukin-6, 31 as well as by transgene-mediated expression of enkephalin in dorsal root ganglia neurons. 32 C-peptide and the glutamate carboxypeptidase II inhibitor treatments alleviated thermal hyperalgesia in type 1 diabetic BB/ Wor rats, 27,33 and taurine in type 2 Zucker diabetic fatty rats. 34 Whereas mechanisms underlying analgesic effect of these agents require further studies, a number of the treatments mentioned here have been reported to counteract glutamate excitotoxicity by reducing glutamate accumulation, 33,35,36 to restore impaired Ca 2ϩ homeostasis and signaling, 37 to inhibit mitogen-activated protein kinase (MAPK) activation, 38 and to counteract production of proinflammatory cytokines.…”
Section: Pathogenesis and Experimental Treatments Of Diabetes-associamentioning
confidence: 91%
“…40 -43 Enkephalin has been shown to activate the presynaptic ␦-opioid receptor and, through inhibition of PKC and p38 MAPK, to prevent the increase in the neuronal Na V 1.7 tetrodotoxin-sensitive voltage-gated sodium channel isoform (which plays a critical role in nociception) in dorsal root ganglia. 32 Thermal hypoalgesia is present in a large proportion of patients with advanced PDN. This condition has been described in STZ-diabetic rats with longer-term (Ն12 weeks) diabetes, 19,44 and in a number of diabetic mouse models, including SVEV129ϫC57BL/6, 45 C57Bl/ 6J, 13,14,46,47 Swiss Webster, 48 -50 129S1/SvImJ, 44 and CD1 51 mice made diabetic with STZ, as well as nonobese diabetic (NOD) mice, 52 leptin-deficient (ob/ob) mice, 53,54 and diabetic Akita mice (V.R.…”
Section: Pathogenesis and Experimental Treatments Of Diabetes-associamentioning
confidence: 99%
See 1 more Smart Citation
“…In this setting, p38 had deleterious effects on neuronal survival after ischemic insults and DOPr activation during preconditioning reduced subsequent activation of MAPK during ischemia, restoring Bcl2/cytochrome c levels and increasing survival Hong et al, 2007). DOPr stimulation in cultured DRG neurons also inhibited p38 activation and the associated increase in Nav1.7 channel expression that was caused by increasing glucose concentrations in the incubation medium (Chattopadhyay et al, 2008). Similar observations were obtained in DRG neurons recovered from streptozotocin-diabetic mice that were injected with a viral vector codifying for proenkephalin.…”
Section: B D-opioid Receptors and Mitogen-activated Protein Kinase Smentioning
confidence: 96%
“…In addition to changes in protein expression, phosphorylation-induce change of conductance or gating property of Na + channels may also lead to enhanced neuronal excitability and NINP (Aurilio et al, 2008). The activation of presynaptic delta-opioid receptor by enkephalin has been reported to prevent the increase in neuronal Na V 1.7 in DRG through inhibition of PKC and p38 (Chattopadhyay et al, 2008). Tumor necrosis factor-(TNF-), a pro-inflammatory cytokine involved in NINP formation (Schafers et al, 2003), was found to enhance TTX-resistant Na + currents in isolated DRG neurons via a TNF receptor 1-and p38-dependent mechanism (Jin & Gereau, 2006).…”
Section: Voltage-gated Namentioning
confidence: 99%